The Polish Constitutional Court from an Attitudinal and Institutional Perspective Before and After the Constitutional Crisis of 2015–2016 - Kobyliński, Konrad (University of Wroclaw. Faculty of Law, Administration & Economics, 2016)
The term "judicial behaviour" refers to what judges do as judges. The scholarship on higher courts has depicted three ideal types of judicial behaviour: legal, attitudinal, and strategic. Most judges see their own behaviour within the framework of the legal model. Other models are successors of legal realism; the theory that suggests judicial decision making is essentially a matter of politics. In the institutional approach scholars examine judicial decisions as part of a political regime. The Polish Constitutional Court (Trybunał Konstytucyjny, TK) was created during the socialist period and still plays a crucial role in the Polish legal and political system. The paper will try to examine the relationship between the changes in the Polish political environment after the transformation and the legal policy imposed by the TK, and how the former impacted the content of the TK’s decisions. The paper will focus, especially, on the disagreement within the TK and the impact of the 2015-2016 constitutional crisis in Poland.
Keywords: sprawiedliwość konstytucyjna; zdania odrębne; polski Trybunał Konstytucyjny; polski kryzys konstytucyjny; rządy prawa